Methane emissions from ruminants fed white clover and perennial ryegrass forages : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Palmerston North, New Zealand - Hammond, Kirsty Joan (Massey University, 2011)
Ruminant enteric methane (CH4) emissions account for ~35% of New Zealand’s total greenhouse gas (GHG) emissions and a commitment has been made for their reduction. Previous research suggested lower CH4 yields (g/kg dry matter intake; DMI) from sheep fed white clover (Trifolium repens) compared to perennial ryegrass (Lolium perenne; ryegrass), and the initial focus was to account for that difference. However, measurements undertaken here showed little difference between diets in CH4 yield. The objective of this thesis was amended to better understand causes of variation in CH4 emissions from ruminants fed white clover and ryegrass forages. A database analysis showed greater variation in CH4 yield from sheep fed ryegrass forages with measured intakes using the SF6 technique, compared to respiration chambers (23.4 ± 5.70 vs. 23.1 ± 2.90 g/kg DMI). The composition of ryegrass fed to sheep predicted <2% and 20% of the variation in CH4 yield when derived from SF6 and respiration chamber techniques, respectively. For cattle, the database of CH4 yields determined by SF6 found ryegrass composition accounted for 13% of the variation. Measurements in respiration chambers of CH4 yield from sheep in three experiments reported here, had similar values for white clover and ryegrass (22.6 g/kg DMI), despite higher concentrations of fibre and less crude protein in ryegrass. Feed composition predicted less than 19% of variation in CH4 yield. Measurements of CH4 emissions from sheep fed white clover or ryegrass at multiples of 0.8 to 2.5 the metabolisable energy requirements for maintenance (MEm) showed a decline in CH4 yield of 3.47 g/kg DMI for each multiple of MEm intake above maintenance. Measurements of rumen function and digesta kinetics, suggested the rate of liquid flow through the gastro-intestinal tract, and molar percentages of propionate were the main drivers of a change in CH4 yield with intake. This research has shown minor effects of forage composition on CH4 yield, and has highlighted the importance of digestive function to account for effects of intake and individual variation on methanogenesis. The benefits of high feed intakes for production will be complemented by a low CH4 yield and low emissions per unit of production.
Keywords: Rumen fermentation; Ruminants; Feeding and feeds; Methane emissions; White clover; Perennial ryegrass; Trifolium repens; Lolium perenne; Forage; Sheep; Cattle; Environmental aspects